2000
DOI: 10.1364/ol.25.001732
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-linewidth narrowing by means of electromagnetically induced transparency

Abstract: Cavity-linewidth narrowing in a ring cavity that is due to the high dispersion and reduced absorption produced by electromagnetically induced transparency (EIT) in rubidium-atom vapor has been experimentally observed. The cavity linewidth with rubidium atoms under EIT conditions can be significantly narrowed. Cavity-linewidth narrowing was measured as a function of coupling beam power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
102
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 12 publications
2
102
3
Order By: Relevance
“…This is analogous to an impedance-matched AC electric circuit in which the load power is maximized and there is no power reflection from the circuit. In section III, we show that the CQED system can be made to act as a perfect photon absorber (without the control laser) or as a near perfect photon transmitter (when the control laser is on and creates the cavity EIT [21][22][23][24][25]). In section IV, we show that when the control laser is tuned to the polariton resonance and suppresses the polariton excitation, the input light fields cannot be coupled into the cavity and are nearly completely reflected from the cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is analogous to an impedance-matched AC electric circuit in which the load power is maximized and there is no power reflection from the circuit. In section III, we show that the CQED system can be made to act as a perfect photon absorber (without the control laser) or as a near perfect photon transmitter (when the control laser is on and creates the cavity EIT [21][22][23][24][25]). In section IV, we show that when the control laser is tuned to the polariton resonance and suppresses the polariton excitation, the input light fields cannot be coupled into the cavity and are nearly completely reflected from the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…is the control frequency detuning. It will be shown that under appropriate conditions, when the control laser is off, the CQED system behaves like a simple cavity QED system with two-level atoms and the perfect photon absorption can be observed in the strong collectivecoupling regime, in which the CQED system acts as a perfect absorber and there is no output light from the cavity [20]; when the control light is on and induces either the cavity EIT [21][22][23][24][25] or the polariton-suppression interference [26], the perfect photon absorption is suppressed and the CQED system acts as a near perfect light transmitter or light reflector to the two input fields. In the rotating frames, the interaction Hamiltonian for the coupled CQED system under the rotating-wave approximation is…”
Section: Introductionmentioning
confidence: 99%
“…One approach to enhance their sensitivity is to insert a highly dispersive medium inside the cavity. For example, coherent population trapping and EIT have been used to reduce the linewidth of a resonator [8][9][10]. Moreover, it has been argued that the scale factor of a ring laser gyro can be reduced or enhanced depending on the presence of a positive or negative dispersion medium inside the cavity [11,12].…”
mentioning
confidence: 99%
“…5(a) is approximately inversely proportional to the frequency-locking coe cient ⌘ ⇠ @ 0 /@! p [58,59]. The significance of ⌘ is that as it increases the slope of the dispersion increases and the EIT transmission window narrows.…”
Section: Resultsmentioning
confidence: 99%